Understanding the discretionary lane-changing behaviour in the connected environment. (March 2020) - Ali, Yasir; Zheng, Zuduo; Mazharul Haque, Md.; Yildirimoglu, Mehmet; Washington, Simon
Highlights: Focused on the connected environment's impact on discretionary lane-changing decision making. Modeled the connected environment's impact on safety associated with DLC manoeuvres. Developed a Generalised Estimation Equation model for gap acceptance. Modelled the duration of discretionary lane-changing. Abstract: Discretionary lane-changing (DLC) is one of the complex driving manoeuvres that requires surrounding traffic information for efficient and safe manoeuvring. The connected environment not only provides such information but also increases situational awareness, which is useful for DLC decision-making. However, the literature is devoid of any concrete evidence of such impact of the connected environment on DLC decision-making. As such, this paper analyses the effects of the connected environment on DLC behaviour. Seventy-eight participants from a diverse background performed DLCs in randomised driving conditions using the CARRS-Q advanced driving simulator. These driving conditions are: baseline (without driving messages), connected environment with perfect communication (fully functioning and uninterrupted supply of driving messages), and connected environment with communication delay (impaired communication). Various key driving behaviour indicators are analysed and compared using a linear mixed model. To analyse the effects of the connected environment on DLC decision-making, two Generalised Estimation Equation (GEE) models are developed for gap acceptance and DLC duration. In addition, a Weibull accelerated failure time hazard-based duration model is developed to investigate the impact of the connected environment on safety associated with DLC manoeuvres. We find that drivers in the connected environment have a larger spacing, larger lead and lag gaps, a longer DLC duration, and a lower acceleration noise compared to the baseline condition. The GEE model on gap acceptance reveals that drivers tend to select relatively bigger gap sizes when the connected environment offers them the subsequent gap information. Similarly, the GEE model for DLC duration suggests that the connected environment increases DLC durations by 2.22 s and 2.11 s in perfect communication and communication delay driving conditions, respectively. Finally, the hazard-based duration model provides insights into the probability of avoiding a lane-changing collision, and indicates that the probability of a lane-changing collision is less in the connected environment driving conditions than in the baseline scenario. Overall, the connected environment improves the DLC driving behaviour and enhances traffic safety.